Prerequisites for HACCP in small-scale poultry production - Muchangos, A. (University of Pretoria, 2012)
Food borne diseases, and more especially diarrheal diseases, are an important cause of morbidity and mortality (WHO, 2007). Food borne diseases due to bacteria in the food usually manifest as episodes of gastro-intestinal disease (South African DVS, 2007). Most of food borne illnesses occurring annually are caused mainly by three bacteria; Campylobacter spp., nontyphoidal Salmonella serovars, and pathogenic Escherichia coli, including E. coli O157:H7 (Zhao et al, 2001; Mead, 2004). The prevalence of food borne pathogens and epidemiological knowledge of the extent, sources, and causative factors that lead to food borne illness remain unknown in many parts of the world. In most developing countries data are not collected on such a basis that an assessment of the amount of illness or the causes can be made, but food borne illness is probably second only to malnutrition as the cause of death among children (Lund et al, 2000). In Mozambique the situation is similar to other developing countries. The risk of eating poultry meat from formal and informal small scale producers processed in the formal abattoirs and at informal points of slaughter is unknown. However, the diarrheal diseases remain an important cause of mortalities according to data from the Mozambique National Ministry of Health.